2017
DOI: 10.1021/acs.joc.7b01406
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of 2,6-Diarylanilinum Cation by Through-Space Cation−π Interactions

Abstract: Energetically favorable cation−π interactions play important roles in numerous molecular recognition processes in chemistry and biology. Herein, we present synergistic experimental and computational physical–organic chemistry studies on 2,6-diarylanilines that contain flanking meta/para-substituted aromatic rings adjacent to the central anilinium ion. A combination of measurements of pKa values, structural analyses of 2,6-diarylanilinium cations, and quantum chemical analyses based on the quantitative molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 49 publications
4
31
0
Order By: Relevance
“…Simple small molecular systems have emerged as good models for studies of through‐space polar‐π interactions. For instance, substituted 2,6‐diaryl aromatic systems enabled detailed physical‐organic investigations on carboxylic acids, pyridines, anilines and phenols (Figure ) . The molecular architecture of the 2,6‐diaryl aromatic system is particularly suitable for examinations of intramolecular polar‐π interactions between a polar group located at the central aromatic ring and the two flanking aromatic rings whose electronic properties can be fine‐tuned by substituents at the distant para position.…”
Section: Introductionmentioning
confidence: 99%
“…Simple small molecular systems have emerged as good models for studies of through‐space polar‐π interactions. For instance, substituted 2,6‐diaryl aromatic systems enabled detailed physical‐organic investigations on carboxylic acids, pyridines, anilines and phenols (Figure ) . The molecular architecture of the 2,6‐diaryl aromatic system is particularly suitable for examinations of intramolecular polar‐π interactions between a polar group located at the central aromatic ring and the two flanking aromatic rings whose electronic properties can be fine‐tuned by substituents at the distant para position.…”
Section: Introductionmentioning
confidence: 99%
“…The observed slope provided the ρ value of +1.1, which is essentially the same as the one found for 2,6diarylanilines and 2,6-diarylpyridines. 21,22 These results indicate that para-substituted donating groups (e.g. OMe, Me) make the neighboring flanking aromatic rings more electron-rich, thus leading to significant stabilization of 2,6-diarylphenols, as manifested by higher pKa values (i.e.…”
mentioning
confidence: 97%
“…We conceived that the arrangement of two flanking aromatic rings around the central phenolic 3 ring in 2,6-diarylphenols enables detailed experimental and computational examinations of proposed through-space OH-π interactions at the unprecedented level of molecular detail. Physical-organic studies on the most related 2,6-diarylcarboxylic acids, 20 2,6-diarylpyridines, 21 and 2,6-diarylanilines 22 revealed that the linear trends in acidities of such systems are a result of through-space effects ( Figure 1). We hypothesized that the two neighboring flanking aromatic rings of 2,6-diarylphenols do not stabilize the protonated form of phenol via through-bond interactions, but rather via through-space OH-π interactions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of aqueous solvation was simulated by means of the conductor like screening model (COSMO) of solvation, as implemented in ADF. The approach has been benchmarked against highly correlated post-Hartree-Fock methods and experimental data and was found to work reliably [44][45][46][47][48][49].…”
Section: Quantum Chemical Analysismentioning
confidence: 99%